Konsep Dasar Epistemologi Pendidikan Multikultural Dalam Islam - Zainun Wafiqatun Niam (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2019)
Education as a means of developing human potential and the formation of a community order must be carried out with the principles of equality and justice. The principle is based on the inevitability that humans live within the sphere of difference. Islamic education as a way of forming human beings, upholds the value of justice as a consequence of one of its roles as khalifatullah on the face of the earth, which is to prosper the universe. One aspect of education that can deliver this goal is the view of multiculturalism in Islamic education. This paper is aimed at looking at the basic concepts of the epistemology of multicultural education in Islam, which ultimately can be implemented in the process of Islamic education. The method used in writing this article is the